2018
DOI: 10.1253/circj.cj-17-0145
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic Delayed Afterdepolarizations Are Promoted by Severe Hypothermia But Not Therapeutic Hypothermia

Abstract: ryanodine receptor (RyR) dysfunction. 16-18 Given clinical observations of increased ventricular ectopy and irritability during SH, frequent triggered arrhythmias would be predicted. 10,19,20 Moreover, although repolarization abnormalities induced by hypothermia are known to promote substrates for re-entrant VF, 21 the effect of hypothermia on VF triggers is poorly understood.Despite the contrast in arrhythmia susceptibility associated with TH vs. SH, there have been very few systematic studies that have inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Fukaya, et al reported in their canine experimental model that calcium-mediated premature beats which triggered VF increased in advanced hypothermic conditions. 25) The mechanisms of triggered premature beats and maintenance of hypothermic VA could not be studied in this study. Third, using a small number of electrodes placed in the wedge preparation may underestimate the change in the myocardial depolarization and repolarization during the hypothermic condition.…”
Section: Discussionmentioning
confidence: 94%
“…Fukaya, et al reported in their canine experimental model that calcium-mediated premature beats which triggered VF increased in advanced hypothermic conditions. 25) The mechanisms of triggered premature beats and maintenance of hypothermic VA could not be studied in this study. Third, using a small number of electrodes placed in the wedge preparation may underestimate the change in the myocardial depolarization and repolarization during the hypothermic condition.…”
Section: Discussionmentioning
confidence: 94%
“…Hypothermia retards the activation and/or inactivation process, leading to ion channel dysfunction. For example, Fukaya et al showed that hypothermia caused Ca i overload and slowing of SR Ca 2+ release kinetics through RyR2 dysfunction in a temperature-dependent manner ( Fukaya et al, 2017 ). Millet et al (2021) reported that hypothermia retarded SERCA2a-mediated Ca 2+ uptake into the SR to facilitate Ca i alternans during tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…In both cold and hot environments, humans may experience atrial or ventricular arrhythmias such as ventricular fibrillation (Fig. 1 A) (Fukaya et al 2017 ; Mackiewicz and Lewartowski 2006 ; review: Antzelevitch and Yan 2010 ). Histamine may cause atrial and ventricular cardiac arrhythmias, even under normothermia (review: Neumann et al 2021b ).…”
Section: Introductionmentioning
confidence: 99%